Synergistic Effects of Coconut Water-Based Liquid Organic Fertilizer and NPK Mutiara Fertilizer on the Growth Parameters of Liberica Coffee Seedlings (Coffea liberica W. Bull ex Hiern): Sinergi POC Air Kelapa Dan NPK Mutiara Terhadap Parameter Pertumbuhan Bibit Kopi Liberika (Coffea liberica W. Bull Ex Hiern) - Iin Arsensi; Asiah Wati; Maria Vianney Buaq; Albertus Albertus (Agrifarm : Jurnal Ilmu Pertanian, 2026)
This study aimed to evaluate the synergistic effect of coconut water-based liquid organic fertilizer and inorganic NPK Mutiara fertilizer on the growth of Liberica coffee seedlings (Coffea liberica W. Bull ex Hiern). The experiment was arranged using a Randomized Block Design (RBD) consisting of two factors with 16 treatment combinations and three replications, resulting in a total of 48 polybags. The first factor was coconut water liquid organic fertilizer, consisting of four levels: P0 = no treatment; P1 = 50 mL/L; P2 = 100 mL/L; and P3 = 150 mL/L. The second factor was NPK Mutiara fertilizer, consisting of four levels: N0 = no treatment; N1 = 50 g/polybag; N2 = 100 g/polybag; and N3 = 150 g/polybag. The observed variables included plant height (cm), stem diameter (mm), and number of leaves. Data were analyzed using Analysis of Variance (ANOVA). Further tests were conducted to determine significant differences among treatments.